Adipose tissue dendritic cell signals are required to maintain T cell homeostasis and obesity-induced expansion. (5th April 2020) - Porsche, Cara E.; Delproposto, Jennifer B.; Patrick, Elise; Zamarron, Brian F.; Lumeng, Carey N.
Abstract: Adipose tissue derived chronic inflammation is a critical component of obesity induced type II diabetes. Major histocompatibility complex II (MHCII) mediated T cell activation within adipose tissue is one mechanism that contributes to this phenotype. However, the contribution of dendritic cells as professional antigen presenting cells in adipose issue has not previously been explored. Using Itgax Cre x MHCII fl/fl (M11cKO) mice we observed adipose tissue specific changes in adipose tissue leukocytes. While there was a complete knockout of MHCII in dendritic cells, MHCII was also absent on the majority of macrophages. This resulted in reduction of TCR expression in CD4 + T cells in obese adipose tissue, and an increase in CD8 + and CD4 + CD8 + double positive T cells with decreased CD4 + T cells independent of diet type. Increased CD8 + cells were not observed in the spleen, suggesting adipose tissue T cell regulation is tissue specific. In vitro studies demonstrated more potent antigen presentation function in adipose tissue dendritic cells compared to macrophages. Obese M11cKO mice had decreased CD11c + adipose tissue macrophages. Despite the changes of immune cellularity in adipose tissue, M11cKO largely did not change inflammatory gene expression in adipose tissue and did not demonstrate differences in glucose and insulin intolerance. Overall MHCII expression on CD11c + cells is important for maintaining CD4 + and CD8 + adipose tissue T cells, but these cellular changes fail to alter inflammatory output and systemic metabolism. Highlights: Adipose tissue dendritic cells are more potent activators of T cells than adipose tissue macrophages. MHCII mediated ATT activation is not required for induction of chronic low grade inflammation in adipose tissue with obesity. MHCII fl/fl x CD11c Cre results in decreased CD4 + and increased CD8 + and CD4 + CD8 + double positive adipose tissue T cells.